2019
DOI: 10.17098/amj.576532
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of Systemic Diseases According to Age and Gender in Patients Admitted to an Oral and Dental Health Care Hospital

Abstract: Objectives: Investigation of systemic disorders of adult patients prior to dental interventions is of great importance in order to take relevant precautions and prevent possible complications. The aim of this study is to determine the frequency and distribution of various systemic diseases in adult patients who admitted to the outpatient clinic of an oral and dental health care hospital. Materials and Methods: Study group included a total of 440 patients, 251 females and 189 males aged between 18 to 80 years w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
1
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
1
1
0
3
Order By: Relevance
“…In our study, a statistically significant association was present between age of patients and the prevalence of systemic diseases with maximum prevalence (2.3%) in the age group of 41-50 years. Our study results were supported by Otkay et al [ 15 ] who reported a similar relationship. Kumar MP S et al [ 16 ] also stated that systemic diseases were more common in older patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, a statistically significant association was present between age of patients and the prevalence of systemic diseases with maximum prevalence (2.3%) in the age group of 41-50 years. Our study results were supported by Otkay et al [ 15 ] who reported a similar relationship. Kumar MP S et al [ 16 ] also stated that systemic diseases were more common in older patients.…”
Section: Discussionsupporting
confidence: 92%
“…92% of patients in our study did not have any systemic disease. Oktay et al detected no systemic diseases in 60% of patients in their study [ 15 ]. In our study, a statistically significant association was present between age of patients and the prevalence of systemic diseases with maximum prevalence (2.3%) in the age group of 41-50 years.…”
Section: Discussionmentioning
confidence: 91%
“…[1][2][3]5,8,9 Literatürde, farklı popülasyonlarda yapılan araştırmalarda ise sistemik hastalık prevalansını, Ashraf ve ark. 6 16 KVS hastalıkları, farklı çalışmalarda en sık görülen sistemik hastalık grubudur. 5,11,14 KVS hastalıklarının prevalansını Ciğerim 3 %14.8, Oktay ve ark.…”
Section: Discussionunclassified
“…5,11,14 KVS hastalıklarının prevalansını Ciğerim 3 %14.8, Oktay ve ark. 16 ise %13.40 olarak rapor etmiştir. Bizim çalışmamızda da literatürdeki çalışmalara benzer olarak en sık görülen sistemik hastalık %13.37 prevalans değeri ile KVS hastalıklarıdır.…”
Section: Discussionunclassified
See 1 more Smart Citation